2003
DOI: 10.1002/anie.200219562
|View full text |Cite
|
Sign up to set email alerts
|

Membership Rules for a Molecular Box: The Admission Process and Protection Provided to Guest Molecules

Abstract: Molecular containers are the smallest possible agents for sensing, sorting, and sequestering ions and molecules. [1] Molecular cages based on transition-metal vertices often easily self-assemble, and those with inorganic frameworks are of special interest because their rigidity, uncommon in organic ligands, [2][3][4][5] could give rise to high selectivity with respect to guest size.Prussian Blue (PB) and its variants [6][7][8] are insoluble cyanometallate polymers consisting of boxlike subunits that exhibit io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 18 publications
(10 reference statements)
2
45
1
Order By: Relevance
“…[22] Copyright (2018), with permission from Nature Publishing Group. [24] Copyright (2003), with permission from Wiley-VCH. quantify and compare the different host-guest interactions.…”
Section: Type II Porous Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] Copyright (2018), with permission from Nature Publishing Group. [24] Copyright (2003), with permission from Wiley-VCH. quantify and compare the different host-guest interactions.…”
Section: Type II Porous Liquidsmentioning
confidence: 99%
“…reported an empty molecular box [{Cp(Co(CN) 3 } 4 (Cp*Ru) 4 ] (Co 4 Ru 4 , Cp*=C 5 Me 5 , Cp=C 5 H 5 ) based on a cyanogroup‐bridged cage with the aid of a templating ion (Figure 4). [24] Co 4 Ru 4 had a neutral, discrete and rigid metal‐cube structure. The central cavity of Co 4 Ru 4 was capable of accommodating small molecules such as K + , Rb + , Cs + , Tl + , NH 4 + , MeNH 3 + , and N 2 H 5 + .…”
Section: Type II Porous Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, we have been able to prepare neutral boxes, the prototype being {[CpCo(CN) 3 ] 4 [Cp*Ru] 4 } (Co 4 Ru 4 ) [8]. This species forms via the EtNH þ 3 -templated reaction of the constituent organometallic building blocks (Eq.…”
Section: Introductionmentioning
confidence: 98%
“…Polymerization could be thus inhibited, and a family of cages with a box-like architecture results. Some early examples showed that the reaction of fac À LMðCNÞ nÀ 3 with LMðH 2 OÞ mþ 3 or LMðMeCNÞ mþ 3 resulted in cyanometallate boxes, ½M 8 ðCNÞ 12 4ðnÀmþÞ , from the displacement of the labile MeCN or H 2 O ligand [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. As part of our interest in this area, we are focusing on the coordination complexes of iron, which have the same components as classic Prussian blue materials and will offer the potential for comparison with classic Prussian blue materials.…”
mentioning
confidence: 99%